Legal Reconstruction of Hadhanah Rights Due to Divorce in Indonesia from a Maqashid Syari’ah Perspective - Farid, Muhammad; Albani, Muhammad Syukri; Lubis, Fauziah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The issue of child custody (Hadhanah) following divorce in Indonesia remains a critical legal concern, particularly in ensuring children's welfare. Indonesian regulations, including Law No. 1 of 1974 and the Compilation of Islamic Law (KHI), govern custody based on the child’s age and impose an obligation on parents to provide financial support. However, these regulations lack sanctions for parents who neglect their responsibilities, leading to concerns over inadequate care, education, and financial support for children. This study aims to analyze the legal reconstruction of Hadhanah rights from the Maqashid Syari’ah perspective to ensure better child protection. The research employs a library research methodology, examining various legal sources, scholarly works, and judicial decisions to assess the existing legal framework and its implementation in judicial practice. The findings reveal that Indonesian courts typically grant custody to the mother for children who have not yet reached the age of discernment (mumayyiz), following normative legal provisions. However, some judges decide contra legem, prioritizing the child’s best interests based on Maqashid Syari’ah. For example, the Padang High Religious Court granted custody to the father, considering the child's welfare. Enforcement of custody decisions involves forcibly placing the child with the designated guardian, while financial support enforcement is executed through asset seizure from non-compliant parents. To enhance child protection, legal reconstruction is necessary through regulatory reforms and judicial discretion. Revisions should include the introduction of sanctions for negligent parents and the establishment of specialized institutions for child welfare. Judicial reform should provide equal custody opportunities for both parents while prioritizing the child's best interests in alignment with Maqashid Syari’ah principles.